An Action Plan for Adaptation in Bangladesh Agriculture under Climate Change - Asaduzzaman, Mohammed; Qamar Munir, Mohammad; Ghulam Hussain, Sk; Khan, Malik Fida A; Abdur Rashid, Mohammad; Rahaman, Ahmmed Zulfiqar; Akand, Md. Kamruzzaman (Center for Environmental and Geographic Information Services, 2016)
This report is the outcome of a study titled 'An Action Plan for Adaptation in Bangladesh Agriculture under Climate Change', carried out with support from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). This report prepared by the Center for Environmental and Geographic Information Services (CEGIS) delineates an action plan to prioritize adaptation options after considering the inputs by experts and scrutiny by stakeholders. It aims to promote precision agriculture and commercialization of crop agriculture with strong institutional and financial footing to tackle climate change.